Insight into the development and competitiveness of male uk-based stand-up paddleboard flatwater distance racing from 2013 to 2017 - Dyer, B. (The Journal of Strength and Conditioning Research, 2021)
An analysis of 2 stand-up paddleboard "distance" events was undertaken to investigate any change in their participation, racing behavior, and whether such events should be approached differently by practitioners. The completion time paddler-to-paddler gap was investigated as a means of assessing the performances in 2 flatwater distance events from 2013 to 2017. The level of participation at these events had not noticeably changed. An analysis indicated that both events did not significantly change in their completion time paddler-to-paddler range from year to year when looking at 3 subgroups (p > 0.05) and did not differ significantly in behavior when normalized against each other (p > 0.05). Post hoc tests revealed that the paddler time gaps at an event held in 2015 were significantly different when compared with all the other years it had taken place (p < 0.05). The use of a performance intensity chart indicated that there was different finishing paddler-to-paddler gap behavior between the 2 events. Ultimately, it is proposed that athletes and coaches should be aware that 2 events with the same generic classification of being designated a "distance event" may warrant different training methodologies and tactical decision-making.